Character Quest: A Mixed-Methods Study of Role-Playing Games and Self-Regulation Skill in Kindergarten - Utami, Rahayu Dwi; Tawandorloh, Ku-Ares (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study investigates the impact of structured role-playing game (RPG) activities on the development of self-regulation skills among kindergarten children. In particular, it examines whether participation in a purpose-designed RPG module (Character Quest) enhances young learners' attention control, emotional regulation, and behavioral inhibition.Design/methods/approach – A convergent parallel mixed-methods design was employed. Quantitatively, 30 kindergarteners (aged 5–6) completed the Self-Regulation Rating Scale before and after an eight-week RPG intervention. Qualitatively, semi-structured interviews were conducted with five participating teachers, and classroom observations and children's play journals were analyzed. Quantitative data were analyzed using paired-samples t-tests and effect-size calculations; qualitative data underwent thematic coding and were integrated via a triangulation matrix.Findings – Quantitative results showed a statistically significant increase in overall self-regulation scores (pre-test M = 2.48, SD = 0.37; post-test M = 3.10, SD = 0.29; t(29) = 8.23, p < .001, Cohen's d = 1.50). Qualitative themes revealed heightened engagement, the transfer of in-game strategies to classroom tasks, and positive teacher observations of improved impulse control and peer collaboration. Integration of both data strands suggests that RPG sessions provide a motivating context for practicing self-regulatory behaviors.Research implications/limitations – While the mixed-methods approach offers robust insights, the small sample size and single-school setting limit generalizability. Future research should explore longitudinal effects across diverse cultural contexts and incorporate control-group comparisons to isolate RPG-specific effects.Practical implications – Educators and curriculum designers may incorporate structured RPG modules as a playful, low-cost strategy to foster self-regulation in early childhood settings. Training teachers to facilitate game-based activities and to scaffold reflection on in-game decisions can maximize skill transfer to everyday classroom behaviors.Originality/value – This study contributes to the growing field of game-based learning by applying a mixed-methods framework to evaluate a tabletop RPG intervention for self-regulation in kindergarten. While previous research has explored digital games and general play-based approaches, this study offers integrated quantitative and qualitative evidence on how structured narrative-driven RPGs can support self-regulatory development in early childhood classrooms.Paper type Research paper